Estabilidade de agregados em Latossolos sob plantas de cobertura em rotação com soja e milho - Borges, Wander Luis Barbosa; De Souza, Isabela Malaquias Dalto; De Sá, Marco Eustáquio [UNESP]; Alves, Marlene Cristina [UNESP] (Revista Brasileira de Ciencias Agrarias, 2016)
The objective was to evaluate the effect of different covers on the stability of soil aggregates in two areas of Oxisols, grown in rotation with crops of soybean and corn. The experiments were installed in Votuporanga, São Paulo, Brazil and Selvíria, Mato Grosso do Sul, Brazil in March 2008. The experimental design was a randomized block with four replicates and the following cover crops in different spending ha-1 seeds, were the treatments: Sorghum bicolor, 6, 7 and 8 kg ha-1; Pennisetum americanum, 10, 15 and 20 kg ha-1; S. sudanense, 12, 15 and 18 kg ha-1; hybrid of S. bicolor and S. sudanense, 8, 9 and 10 kg ha-1; Urochloa ruziziensis, 8, 12 and 16 kg ha-1; plus, control treatment with spontaneous vegetation. We evaluated the dry matter yield of different covers and were separate classes of soil aggregates and calculated the average diameter. It is noted that the cover crops had similar behavior on aggregates stability in the surface layer, and in the greater depth, the S. sudanense was more efficient in improving the class mean diameter between 2.0-1.0 mm, in Votuporanga, and the P. americanum was more efficient from 4.0 to 2.0 mm and 2.0-1.0 mm in Selvíria. Lower spending seeds was more promising on aggregate stability.
Aggregate stability in Oxisols under cover crops in rotation with soybean and corn
Keywords: Glycine max; Sustainable soil management; Zea mays